Efeitos dos treinos físico e mental no ensino do rolamento para a frente em alunos com deficiência mental - Tonello, Maria Georgina Marques (2007)
People with mental retardation usually present motor development delays. Nevertheless, these delays seem to be more often related to cognitive factors such as attention and comprehension than to motor or mental deficits. Strategies have been developed to teach motor skills to this population. One of the existing strategies is mental training, which is based on imagining the movement to be executed without the presence of the physical movement. The general objective of this doctoral dissertation was to apply a procedure based on physical and mental training to the teaching of rolling forward, a basic skill for artistic gymnastics practitioners, and to verify its effects in mentally retarded students. In experiment 1 there were two subjects (P1 and P2) aged 15 and 20 respectively, enrolled in a school for the mentally retarded. A single-subject experimental design with alternating treatments was applied. The rolling forward skill was divided in four phases. The results showed that P1 learned all the phases of forward rolling, whereas P2 learned partially phases I and II of the skill taught. We believe that the difficulty found by this participant was due to his motor difficulties, once he also presented an associated physical handicap. The purpose of experiment 2 was to apply the mental training procedure and verifying their effects in the forward rolling learning process in three students aged 12, 12 and 16, respectively, all of them with mental retardation. The experimental design applied was of the single subject in a multiple baseline design. The participants of this study learned all phases of forward rolling, and even though they presented different performance levels, all of them benefited from the strategy used. We realized that the mental training elicited other behaviors from the participants like: following rules, self-conversation, attention, concentration and relaxation. To understand the aspects that affect the use of mental training and to establish experimental designs to investigate this strategy were some of the contributions of this work.